2014
DOI: 10.1002/jms.3366
|View full text |Cite
|
Sign up to set email alerts
|

Desorption/ionization efficiencies of triacylglycerols and phospholipids via EASI‐MS

Abstract: Knowledge of the major effects governing desorption/ionization efficiency is required for the development and application of ambient mass spectrometry. Although all triacylglycerols (TAG) have the same favorable protonation and cationization sites, their desorption/ionization efficiencies can vary dramatically during easy ambient sonic-spray ionization because of structural differences in the carbon chain. To quantify this somewhat surprising and drastic effect, we have performed a systematic investigation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…The spray droplets hit the surface of the thin film of electrolyte solution, now thinner than 1 mm due to the N 2 nebulizing gas pressure, on the surface of the working electrode. Much like in DESI-MS and easy ambient supersonic spray 2830 MS, tinier secondary microdroplets are directed into the mass spectrometer 31,32 and are analyzed with an LTQ Orbitrap XL hybrid mass spectrometer (Thermo Fisher Scientific, San Jose, CA) where the m / z ratio is determined utilizing the high mass accuracy and high resolving power of the Orbitrap mass analyzer. 33 …”
Section: Methodsmentioning
confidence: 99%
“…The spray droplets hit the surface of the thin film of electrolyte solution, now thinner than 1 mm due to the N 2 nebulizing gas pressure, on the surface of the working electrode. Much like in DESI-MS and easy ambient supersonic spray 2830 MS, tinier secondary microdroplets are directed into the mass spectrometer 31,32 and are analyzed with an LTQ Orbitrap XL hybrid mass spectrometer (Thermo Fisher Scientific, San Jose, CA) where the m / z ratio is determined utilizing the high mass accuracy and high resolving power of the Orbitrap mass analyzer. 33 …”
Section: Methodsmentioning
confidence: 99%
“…The spray droplets hit the surface of the thin film of electrolyte solution, now thinner than 1 mm owing to the N 2 nebulizing gas pressure, on the surface of the working electrode. Much like in desorption electrospray ionization DESI‐MS15, 16 and easy ambient supersonic spray MS1719, tinier secondary microdroplets are directed into the mass spectrometer20, 21 and are analyzed with an LTQ Orbitrap XL hybrid mass spectrometer (Thermo Fisher Scientific, San Jose, CA), where the m / z ratio is determined by utilizing the high mass accuracy and high resolving power of the Orbitrap mass analyzer 22…”
Section: Methodsmentioning
confidence: 99%
“…500 nm radius) and is collected on aP ts ubstrate (5 mmr adius) separated from the Pt tip by af ew hundred nanometers.B yv arying the separation, the dimerization process was shown to follow second-order kinetics with arate constant of 2.5 10 8 m À1 s À1 .S ECM experiments could be performed at DMA concentrations as high as 0.4 mm in acetonitrile,u nder which conditions the half-life is 10 ms. At greater concentrations,the dimerization is reported to be too fast to obtain good collection efficiency. Thes pray droplets hit the surface of the thin film of electrolyte solution, now thinner than 1mmo wing to the N 2 nebulizing gas pressure,o nt he surface of the working electrode.M uch like in desorption electrospray ionization DESI-MS [15,16] and easy ambient supersonic spray MS [17][18][19] ,t inier secondary microdroplets are directed into the mass spectrometer [20,21] and are analyzed with an LTQOrbitrap XL hybrid mass spectrometer (Thermo Fisher Scientific,San Jose,CA), where the m/z ratio is determined by utilizing the high mass accuracya nd high resolving power of the Orbitrap mass analyzer. [1] This study suggests that many other short-lived electrochemical intermediates could be identified and studied by this means since MS is ageneral detector with high chemical specificity,unlike electrochemical detectors.…”
mentioning
confidence: 99%
“…Thes pray droplets hit the surface of the thin film of electrolyte solution, now thinner than 1mmo wing to the N 2 nebulizing gas pressure,o nt he surface of the working electrode.M uch like in desorption electrospray ionization DESI-MS [15,16] and easy ambient supersonic spray MS [17][18][19] ,t inier secondary microdroplets are directed into the mass spectrometer [20,21] and are analyzed with an LTQOrbitrap XL hybrid mass spectrometer (Thermo Fisher Scientific,San Jose,CA), where the m/z ratio is determined by utilizing the high mass accuracya nd high resolving power of the Orbitrap mass analyzer. Thes pray droplets hit the surface of the thin film of electrolyte solution, now thinner than 1mmo wing to the N 2 nebulizing gas pressure,o nt he surface of the working electrode.M uch like in desorption electrospray ionization DESI-MS [15,16] and easy ambient supersonic spray MS [17][18][19] ,t inier secondary microdroplets are directed into the mass spectrometer [20,21] and are analyzed with an LTQOrbitrap XL hybrid mass spectrometer (Thermo Fisher Scientific,San Jose,CA), where the m/z ratio is determined by utilizing the high mass accuracya nd high resolving power of the Orbitrap mass analyzer.…”
mentioning
confidence: 99%
See 1 more Smart Citation